College Students’ Perception of Using Canva in English Writing Class - I Putu Dipta Priyatna; Ni Komang Arie Suwastini; Gede Rasben Dantes (Indonesian Journal Of Educational Research and Review, 2023)
The exponential development of technology has provided tools that can support the teaching and learning process. The present study aimed to analyze college students' perceptions of using the graphic design tool Canva to support their English Writing Class. The study was designed as qualitative research. The subject of this study involving sixteen students in a private college. The data were collected using a questionnaire. After collecting the data, it was analyzed qualitatively. The results were then compared with theoretical and empirical materials to assist the researcher in analyzing the obtained data for discussion. The study revealed that 86.4% of the students had positive perceptions concerning the usefulness, ease of access, and suitability of Canva for supporting English writing skills, with 47.0% of the students strongly agreed, 39.4% agreed, and only 13.5% of them partially agreed. The study also revealed that students encountered challenges during the implementation of Canva in English Writing class, primarily related to their readiness to use the features provided by Canva for supporting their writing process. These findings imply that mastery of the tool's features is crucial for gaining optimum benefits in using Canva to improve students' writing skills.